Keeping Track of the Genealogy of Heterozygotes Using Epigenetic Reference Codes and Breeding Tables - Liberati, Anna Sara; Calcaprina, Barbara; Adriani, Walter (Frontiers in Behavioral Neuroscience, 2022)
Studying neurobehavioral consequences of the hypofunctional dopamine transporter (DAT) across several generations entails the need to monitor allelic transmission to offspring, taking into account both maternal and paternal inheritance. Since each type of heterozygote expresses differential phenotypes, based on lineage of inheritance for wild and mutated alleles (from male or female ancestors), it is important to track transgenerational epigenetic effects. We deemed it essential to assign specific abbreviations identifying their characteristics. Therefore, we devised a Mendelian-inspired table to keep track of these. Starting from two progenitors (WT and KO) we named resulting heterozygous progenies MAT and PAT to differentiate them based on inheritance of the wild allele (from the mother or father). Tracing subsequent generations, similar logic has been followed: if coupling HET dams with KO males, initials “M” [(grand)maternal] and “P” [(grand)paternal] are kept, but “AT” is turned into “IX” (MIX and PIX), while if breeding HETs with WTs, “M” is changed to “W” resembling an upside down “M” and “P” to “S” for “sperm” (WAT and SOT). To underline the development within “hyperdopaminergic-uterus” a central letter “U” is added (MUX, PUX, and QULL), while a Greek initial (μAT, μIX, and νIX) underlines the uterine-worsened origin of the allele. In HET × HET breeding (GIX and DIX), the mutated allele can be inherited from both sides of the genealogical line. However, when the mother is MAT, wild and mutated alleles encounter for the first time, causing putative anomalies in the progeny. Replacing dam with a second-generation female (MIX and MUX) may mitigate epigenetic effects on third-generation offspring; therefore suffixes (“-f,” “-fu,” “-ϕ,” and “-ϕu”) emphasize that subsequent-generation dams imply that the alleles already encountered in HET (rather than WT) grand-dams.